2023
DOI: 10.1007/s10988-022-09369-8
|View full text |Cite
|
Sign up to set email alerts
|

A semantics of face emoji in discourse

Abstract: This paper presents an analysis of face emoji (disc-shaped pictograms with stylized facial expressions) that accompany written text. We propose that there is a use of face emoji in which they comment on a target proposition expressed by the accompanying text, as opposed to making an independent contribution to discourse. Focusing on positively valenced and negatively valenced emoji (which we gloss as happy and unhappy, respectively), we argue that the emoji comment on how the target proposition bears on a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Since their creation by a Japanese telecommunication company, the Unicode Consortium has helped to regulate coding practices for a set of emoji characters that can operate across a variety of technologies. In 1995 there were only 75 emoji, while in 2023 there are now 3,500 emoji with, some claim, close to 10 billion emoji sent every day (Grosz et al 2023).…”
Section: Emoji and Communicative Actionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since their creation by a Japanese telecommunication company, the Unicode Consortium has helped to regulate coding practices for a set of emoji characters that can operate across a variety of technologies. In 1995 there were only 75 emoji, while in 2023 there are now 3,500 emoji with, some claim, close to 10 billion emoji sent every day (Grosz et al 2023).…”
Section: Emoji and Communicative Actionmentioning
confidence: 99%
“…A body of work is emerging that draws on Conversation Analysis (König 2019) and discursive approaches, particularly speech act theory (Skovholt, Grønning and Kankaanranta 2014;Sampietro 2016cSampietro , 2019Herring and Dainas 2017), to move away from an interest in the 'cultural use' of emoji and towards an examination of the localised sequential practices of their application. Studies have illustrated how emoji may be used for the purposes of creating 'alignment' (e.g., 👍🤝😋🥳) and 'disalignment' (e.g., ⚔🚫❌😡) between turns (Gestadnyk 2021), or, in other terminology, a positive or negative 'valance' (Grosz et al 2023), and have shown that users often treat the meaning of different emoji as interchangeable, so that 👌and 👍might mean the same thing (just as a gestural 'ok' sign or a 'thumbs up' might). The sequential placement of emoji can help users to see the specific types of interactional work that they achieve.…”
Section: Emoji and Communicative Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formal models and introspective methods are now routinely applied to sign languages (Sandler & Lillo‐Martin 2006), a standard if understudied linguistic object. Within visual communication, they are increasingly applied to nonstandard objects as well, such as gestures and even emojis (Grosz et al., to appear; Schlenker, 2018). In literature, the grammatical paradigm helped analyze a literary style, “Free Indirect Discourse,” which mixes properties of direct and indirect discourse (Banfield, 1982).…”
Section: The Fruitfulness Of the Grammatical Paradigmmentioning
confidence: 99%